Effect of dietary stevia and ginger extracts on laying performance, fertility, hatchability, and serum biochemical parameters in laying Japanese quails exposed to heat stress - Bayril, T.; Akdemir, F.; Gurgoze, S.; Orhan, C. (Kielanowski Inst Animal Physiology Nutrition, 2023)
The aim of this study was to determine the effect of various levels of supplemental stevia and ginger extracts (SGE) on laying performance, fertility, hatchability, and serum biochemical parameters in laying Japanese quails exposed to heat stress. SGE doses were added at the following levels: 0 (control), 0.5 (T1), 1.0 (T2), and 1.5% (T3) of the diet. In SGE-supplemented quails, feed intake (P < 0.0001), egg production (P < 0.0001), and egg weight (P < 0.002) were significantly the highest in the treatment groups (days 1-90). Feed conversion ratio (P < 0.0001) was lower in the treatment groups compared to the control group. The fertility index was higher in all experimental groups (P < 0.05). The weights of hatching eggs were higher in groups T2 and T3 (P < 0.0001). Egg weight in the laying period was higher in the 2nd month in control and group T1, and in the 2nd and 3rd month in groups T2 and T3 (P < 0.0001; P < 0.05). Hatched chick weights were higher in groups T2 and T3 (P < 0.0001). Serum aspartate aminotransferase levels in quails of group T3 were significantly lower than in the other groups (P < 0.01). Serum glucose and cholesterol levels were the lowest in groups T2 and T3 (P < 0.05). Serum triiodothyronine levels in the treatment groups were significantly lower (P < 0.01). In conclusion, these results suggested that dietary SGE improved laying performance, fertility, and hatchability, as well as mitigated the negative effects of heat stress on selected biochemical parameters in quails exposed to high environmental temperature.
Keywords: fertility; hatchability; heat stress; Japanese quails; laying performance; stevia and ginger extract